Dark Academia: How Old Inequalities Are Being Retold in a Global Youtube Learning Phenomenon - Drozdowicz, Jarema (Adam Marszałek, 2024)
This study examines the emerging trend in online learning related to the phenomenon of YouTube and lo-fi music channels regarded as an aid in the process. The main object of study are the so-called Dark Academia streaming forms. This phenomenon is being examined through the perspectiveof critical cultural studies and qualitative research. The research sample is constituted here by the selected channels providing specific content to online learners. The significance of the study is however not just related to the Dark Academia as an internet phenomenon, but also as a contemporary cultural reflection of learning strategies.